Implementation of the Introduce Connect Apply Reflect Extend (ICARE) Model Learning Flow in developing online modules based on U-Learning Class LMS - Kustiyowati Kustiyowati; Eric Dwi Putra; Pascalian Hadi Pradana; Eges Triwahyuni (Postgraduate, University of Mataram, 2024)
Online learning has started to be used since the emergence of internet technology and became increasingly popular when the Covid 19 pandemic hit. Online learning during the pandemic has given rise to many unique problems for both lecturers and students, such as limitations in presenting material in the sense that the material presented is monotonous and uninteresting, the difficulty of building activity, the difficulty of creating interaction between lecturers and students and between students. Online learning is more stressful than studying in a regular classroom because students are trapped studying alone, the absence of clearly structured learning steps makes it difficult for students to focus on studying. The aims of this research are: to determine the design of an online learning module with an ICARE learning flow based on the U-Learning Class LMS, to determine the feasibility of an online learning module with an ICARE learning flow based on the U-Learning Class LMS. This research uses a Research and Development (R&D) for Education design with the stages of Analysis, Design, Development, Implementation and Evaluation. All stages have been completed and resulted in an online learning module with an LMS-based ICARE learning flow in the Learning Media course which has met the eligibility criteria as a learning resource for use in learning.